Environmental assessment of amending the Amager Bakke incineration plant in Copenhagen with carbon capture and storage - Bisinella, V (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
Amending municipal solid waste incineration with carbon capture and storage (CCS) is a new approach that can reduce the climate change impacts of waste incineration. This study provides a detailed analysis of the consequences of amending the new Amager Bakke incinerator in Copenhagen (capacity: 600,000 tonnes waste per year) with CCS as a post-combustion technology. Emphasis is on the changes in the energy flows and outputs as well as the environmental performance of the plant; the latter is assessed by life cycle assessment. Amending Amager Bakke with CCS of the chosen configuration reduces the electricity output by 50% due to steam use by the capture unit, but introducing post-capture flue gas condensation increases the heat output utilized in the Copenhagen district heating system by 20%. Thus, the overall net energy efficiency is not affected. The CCS amendment reduces the fossil CO2 emissions to 40 kg CO2 per tonne of incinerated waste and stores 530 kg biogenic CO2 per tonne of incinerated waste. Potential developments in the composition of the residual waste incinerated or in the energy systems that Amager Bakke interacts with, do not question the benefits of the CCS amendment. In terms of climate change impacts, considering different waste composition and energy system scenarios, introducing CCS reduces in average the impact of Amager Bakke by 850 kg CO2-equivalents per tonne of incinerated waste. CCS increases the environmental impacts in other categories, but not in the same order of magnitude as the savings introduced within climate change